Toward astrometric calibration of ultrawide‐field images. Issue 5 (10th September 2018) - Bednar, J.; Skala, P.; Pata, P.
Abstract : In this paper, we introduce a new method of astrometric calibration tailored especially for ultrawide‐field systems like WILLIAM. The standard astrometric solution often fails to provide any result if the processed image contains a large amount of distortion, such as from a fisheye lens. Some algorithms yield the result, but the accuracy is satisfactory only at the center of the field of view. This work analyzes such images and proposes a new method that leads to much higher accuracy and success ratio of the calibration.